A Systematic Review of Critical Thinking Assessment Instruments in Junior High School Science Education: Trends, Effectiveness, and Challenges - Barid, Siti Shofa Assyifa’ul Qulbi; Gunawan, Arvidhea Safira; Yusmar, Firdha; Astuti, Soekma Yeni; Wahyuni, Sri (Science Education and Application Journal, 2025)
A Systematic Review of Critical Thinking Assessment Instruments in Junior High School Science Education: Trends, Effectiveness, and Challenges. This systematic literature review, conducted using the PRISMA method, synthesizes research on the development of critical thinking assessment instruments in junior high school science education between 2016 and 2025. Secondary data were obtained through the Publish or Perish application with sources from Google Scholar, keywords include science learning, assessment instruments, and critical thinking. By analyzing 7 peer-reviewed national journals, the study evaluates the validity, reliability, and effectiveness of these tools in enhancing students' critical thinking skills. The findings highlight diverse assessment models, their impact on student learning outcomes, and the challenges faced by educators in implementing these tools. This review offers recommendations for improving the design and application of critical thinking assessments in science curricula.